Relationship Between Life Satisfaction And Mental Health Among College Students Of Hardoi District Of Uttar Pradesh - Verma, Anju; Kishore, Priyanka; Thappa, Seema Rani; Verma, Suman (Journal of Neonatal Surgery, 2025)
This study investigates the levels of life satisfaction and mental health, as well as the relationship between life satisfaction and mental health among college students in Hardoi district of Uttar Pradesh. The sample consisted of 120 participants aged between 17 to 21, who were selected using a random sampling technique. The study utilizes the Life Satisfaction Scale by Q. G. Alam and Ramji Srivastava, as well as the Positive Mental Health Inventory, developed by Dr. C. D. Agashe and R. D. Helode, for assessing mental health. The mean and standard deviation were used to determine the significance of life satisfaction and mental health. The relationship between the relevance and strength of the two variables was assessed using Pearson correlation analysis. The findings revealed a significant, perfect positive correlation between life satisfaction and mental health (r = 1.00, p < 0.01), indicating that individuals who were more satisfied with their lives also experienced better mental health. The study suggests that changes in life satisfaction are similarly associated with changes in mental health